Changes of the Transverse Occlusal Relationships Resulting from Upper Posterior Teeth Intrusion By Using Different Therapeutic Techniques During Anterior Open-Bite Treatment -A Comparative Study On The Study Casts- (Journal of Hama University, 2019)
Background & Objective: The present study aims to assess the effect of upper posterior teeth intrusion using different techniques in the improvement of the amount of  upper and  lower dental arch width, upper basal bone width during skeletal anterior open bite treatment.Methods & Materials: The study sample consisted of 60 anterior open bite patients, ages between (12.5-18.7 yrs). Posterior bite plates have been applied in all patients, and then randomly divided into four groups according to the intrusion method: miniplates, miniscrews, high pull headgear, and a control group. The following variables are examined in this study: upper and lower arch width, basal bone width of the upper arch at premolars and molars region on the study casts.Results: The results show an increase in the amount of anterior and posterior arch width  significantly for miniplates, miniscrews, and high pull headgear groups. Furthermore, high pull headgear group show significant increase in the upper basal bone width compared with the remaining groups. Also significant changes occur on the lower arch width in the high pull headgear group.Conclusion: Upper posterior teeth intrusion by using temporary anchorage devices (TADs) and high pull headgear is an effective means for increasing upper arch dimensions in the transverse direction during anterior open-bite treatment. Whereas, using high pull headgear for posterior teeth intrusion could lead to increase in the width of the upper basal bone and dimensions of the lower dental arch